Geofence alerts application with gps tracking for children monitoring - Mohd Izham, Mohd Jaya; Xin Tong, Goh (2021)
Infamous cases of Malaysia child victim. 2004, Nurul huda, 11 years, raped multiple time, sodomized and strangled. 2008, Burin jazlin. 8 years, dead body stuffed in bag.Cucumber and eggplant inserted into private part. 2013, Nurul nadirah, 4 years, strangled to death. Dead body burned. 2018. Siti masitah, 11 years, head severed. Organs removed.